Prognostic value and therapeutic implications of expanded molecular testing for resected early stage lung adenocarcinoma. (May 2020) - Kneuertz, Peter J.; Carbone, David P.; D'Souza, Desmond M.; Shilo, Konstantin; Abdel-Rasoul, Mahmoud; Zhao, Weiqiang; Williams, Terrance M.; Jones, Daniel; Merritt, Robert E.
Highlights: The expansion of molecular testing increases the detection of mutations. Actionable mutations can be detected in nearly half of resected patients. KRAS and BRAF are associated with recurrence and worse survival after surgery. Increasing detection of mutations create opportunity for adjuvant therapy trials. Abstract: Objectives: This study aimed to evaluate the prognostic and potential therapeutic value of expanded molecular testing of resected early-stage lung ACA. Methods: We analyzed 324 patients who underwent lobectomy and lymphadenectomy for clinical Stage I&II lung ACA between 2011-2017. Molecular testing was routinely performed, first by PCR-based Sanger sequencing and FISH and then expanded to a 20 and then 50-gene next generation sequencing (NGS) panel. The frequency of mutations by testing method and their association with disease-free (DFS) and overall survival (OS) were tested. Results: A total of 241 patients (74.4%) had at least one somatic mutation detected, with KRAS exon 2 (38.1%) and EGFR (17.9%) being the most common. TP53 was the most frequent co-existing mutation. Detection of at least one mutation increased from 49% with selective PCR/FISH testing to 82% with limited NGS/FISH, and 91% with extended NGS/FISH (p < 0.001). The rate of actionable mutations increased from 18% to 32% and 45% with expansion of molecular testing, respectively (p = 0.001). Using NGS, an additional 10 cases with EGFR mutations, and other rare mutations were found, including BRAF (5.9%), MET (5.6%), ERBB2 (4.1%), PIK3CA (2.3%), and DDR2 (2.1%). The expansion of FISH testing resulted in one additional detection of ROS1 and RET (1%) rearrangement. KRAS mutation was associated with worse DFS (HR 1.87; 95%CI 1.14–3.06) and OS (HR 2.09; 95%CI 1.11–3.92). BRAF mutation detected in NGS tested patients was also associated with decreased DFS (HR3.80; 95%CI 1.46–9.89) and OS (HR 7.37; 95%CI 2.36–22.99) on multivariate analysis. Conclusion: The expansion of molecular testing has resulted in a substantial increase in the detection of potentially therapeutically significant mutations in resected early-stage ACA. KRAS and BRAF mutation status by NGS was prognostic for relapse and survival. These data emphasize opportunities for clinical trials in a growing number surgical ACA patients with available targeted therapies.